Terminologia utilizada por enfermeiros nas práticas e ações não farmacológicas na dor crônica em indígena do distrito sanitário especial indígena do Amazonas - Lago, Lívia Jatobá do (Brasil, 2024)
Objective: To identify the terms used by nurses in chronic pain care for indigenous people in the seven Special Health Districts of Amazonas. Methodology: This is a descriptive exploratory study with nurses who work in the Special Indigenous Health Districts of Amazonas. The data was collected between June and December 2022 through focus groups. Results: Processing through the Poronto tool resulted in 1,963 terms with 4,992 repetitions, of which 125 terms were included in the Bank of specialized nursing language terms for non-pharmacological management of chronic pain in indigenous people after inclusion in accordance with the pre-established conditions. For correlation and definition, CIPE 2019/2020 (38 terms) was used as the primary source, as it is the most up-to-date version translated into Brazilian Portuguese. Other sources used were: Health Descriptors (42 terms), Houaiss Dictionary of the Portuguese Language version 2009 (42 terms), standardized documents from the Brazilian Ministry of Health and scientific articles (3 terms). Conclusion: The objectives of this study were achieved because it identified and listed the terms used by nurses in the non-pharmacological management of chronic pain in indigenous people, in order to collaborate with the further instrumentalization of this language in a larger study, to which this research is related.